2018
DOI: 10.1136/postgradmedj-2018-135644
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat is associated with elevation of serum alanine aminotransferase and gamma glutamyltransferase in middle-aged Chinese adults

Abstract: Background Elevation of hepatic enzymes is associated with insulin resistance, dyslipidaemia and obesity. However, the factors behind elevation of liver enzymes remain unclear. The aim of this study was to compare the role of abdominal visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) in relation with serum alanine aminotransferase (ALT) and gamma glutamyltransferase (GGT) in middle-aged Chinese adults.Methods We performed a cross-sectional study on 959 adults aged 40–65 without hepatitis. VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…association of GGT with WC and not BMI is in keeping with a recent cross-sectional study among Chinese adults [34]. This suggests that visceral adipose tissue, as measured by WC, better correlates with GGT than subcutaneous adipose tissue; the latter identified by BMI and representing general adiposity.…”
Section: Plos Onesupporting
confidence: 88%
“…association of GGT with WC and not BMI is in keeping with a recent cross-sectional study among Chinese adults [34]. This suggests that visceral adipose tissue, as measured by WC, better correlates with GGT than subcutaneous adipose tissue; the latter identified by BMI and representing general adiposity.…”
Section: Plos Onesupporting
confidence: 88%
“…Among hepatitis-positive donors (400 HBV positive and 67 HCV positive), only 0.75% (3/400) of HBV-positive donors and 13.43% (9/67) of HCV-positive donors had elevated ALT levels (Table 2). These results suggest that ALT testing adds little risk reduction value for transfusiontransmitted diseases, which is in line with results from previous studies in other countries [21][22][23][24] . During the 7year observation period, 10.76% (291 donations) of excluded blood were discarded only due to high ALT levels.…”
Section: Discussionsupporting
confidence: 91%
“…Lawlor et al (45) similarly reported in 2005 that PA decreased levels of ALT. Liver function has previously been associated with the distribution of regional fat (46). In results consistent with those of earlier studies, we also found that changes in the lipid‐transport protein apolipoprotein A and high‐density lipoprotein cholesterol from PA (47,48) were partially responsible for reductions in adipose tissue.…”
Section: Discussionmentioning
confidence: 99%